Cost of production of food crops: St. James - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The costs presented in this publication correspond to the costs of labour and inputs directly used in the production of the crop (variable cost). The data presented in this publication can be improved further but at the expense of delays in the release of the information to you.